2017
DOI: 10.1186/s13017-017-0153-2
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitative Endovascular Balloon Occlusion of the Aorta in trauma: a systematic review of the literature

Abstract: AimsResuscitative endovascular balloon occlusion of the aorta has been a hot topic in trauma resuscitation during these last years. The aims of this systematic review are to analyze when, how, and where this technique is performed and to evaluate preliminary results.MethodsThe literature search was performed on online databases in December 2016, without time limits. Studies citing endovascular balloon occlusion of the aorta in trauma were retrieved for evaluation.ResultsSixty-one articles met the inclusion cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 39 publications
0
51
0
3
Order By: Relevance
“…Its effectiveness for trauma patients has been evaluated in many large-scale studies [913]; however, the evidence base is weak and clear indications are lacking. Furthermore, although the time and place of balloon insertion, zone of balloon inflation, and inflation cutoff time are very important, they are heterogeneous factors [11, 1418]. In addition, while it has been conceivable that REBOA may be effective in patients with severe trauma when integrated with surgery or interventional radiology (IVR) without delay [9], it remains challenging to successfully perform REBOA in patients with severe multiple torso traumas.…”
Section: Introductionmentioning
confidence: 99%
“…Its effectiveness for trauma patients has been evaluated in many large-scale studies [913]; however, the evidence base is weak and clear indications are lacking. Furthermore, although the time and place of balloon insertion, zone of balloon inflation, and inflation cutoff time are very important, they are heterogeneous factors [11, 1418]. In addition, while it has been conceivable that REBOA may be effective in patients with severe trauma when integrated with surgery or interventional radiology (IVR) without delay [9], it remains challenging to successfully perform REBOA in patients with severe multiple torso traumas.…”
Section: Introductionmentioning
confidence: 99%
“…However, complications developing around the site proximal to the occlusion, such as the possibility of increase in bleeding in the site proximal to the occlusion and the side effects of hyperperfusion, have hardly been studied to date. A systematic review [2] of REBOA, which included 61 articles and 1355 patients, showed that complications of the site proximal to the occlusion occurred only in one patient (0.07%) [3]. …”
Section: Introductionmentioning
confidence: 99%
“…Introduced by a femoral artery sheath, an endovascular balloon is inflated in the aorta, occluding the vessel and acting as an endovascular clamp (Figure 2). REBOA has been demonstrated to be efficacious in a large human case series 12. A prospective registry of 114 patients with critical haemodynamic instability in the US armed forces confirmed that in-hospital REBOA might be a viable alternative to immediate resuscitative thoracotomy (RT) for achieving rapid proximal control.…”
Section: Resuscitative Endovascular Balloon Occlusion Of the Aortamentioning
confidence: 98%